2014
DOI: 10.1139/cgj-2013-0263
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-continuum analysis of monotonic pile penetration in crushable sands

Abstract: This paper presents numerical results from a two-dimensional discrete element method (DEM) simulation study on the monotonic pile installation in crushable sands. The particle breakage was included in the model by setting a crushable zone around a pile that was filled with parallel-bonded agglomerates. In the other part of the model, rigid, unbreakable particles are used to minimize the computational cost. Parametric studies were carried out to examine the effects of initial in situ vertical stress, soil void … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The average stress in a group is found using a similar averaging procedure based on the measurement logic in PFC 2D (Itasca Consulting Group 2008) and the position of each group is represented by the average coordinates of all particles within the group. It should be pointed out that the stress measurements were made on particle groups identified on the undeformed configuration prior to the pile penetration in this study, which is different from the stress measurements based on sampling windows defined on the deformed configuration in the previous study (Wang and Zhao 2014). This is because the current way of stress measurement allows a direct comparison with the experimentally measured stress data from the laboratory model pile test (Jardine et al 2013b), in which the stress sensors were embedded within the sand mass before pile penetration.…”
Section: Group-based Stress Measurementmentioning
confidence: 81%
See 2 more Smart Citations
“…The average stress in a group is found using a similar averaging procedure based on the measurement logic in PFC 2D (Itasca Consulting Group 2008) and the position of each group is represented by the average coordinates of all particles within the group. It should be pointed out that the stress measurements were made on particle groups identified on the undeformed configuration prior to the pile penetration in this study, which is different from the stress measurements based on sampling windows defined on the deformed configuration in the previous study (Wang and Zhao 2014). This is because the current way of stress measurement allows a direct comparison with the experimentally measured stress data from the laboratory model pile test (Jardine et al 2013b), in which the stress sensors were embedded within the sand mass before pile penetration.…”
Section: Group-based Stress Measurementmentioning
confidence: 81%
“…To achieve the same initial stress distribution as in the crushable zone, the density of disks is set to 2200 kg/m 3 in the uncrushable zone. More details about the model generation can be found in Wang and Zhao (2014).…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the small-scale laboratory tests, Discrete Element Method (DEM) has been widely utilised in recent years to investigate the behaviour of geomaterials at the grain-scale which provides valuable information about the grain kinematics, force and displacement fields, contact force network and fabric evolution (Shang et al 2018;Saadat and Taheri 2020;Shen et al 2020;Tran et al 2020). The importance of grain-scale investigation in modelling the interface behaviour and the associated micro-mechanisms has been highlighted in several studies (Jiang et al 2008(Jiang et al , 2014O'Sullivan et al 2008;Butlanska et al 2014;Wang and Zhao 2014). Recently, Lambert and Coll (2014) indicated that it is possible to reproduce the experimental results of the direct shear testing of irregular rock interfaces using the commercially available DEM software PFC 3D .…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge only limited research on the simulation of the soilcone penetrometer was reported in the literature, particularly in agricultural soils. Wang and Zhao (2014) and Tanaka et al (2000) used the DEM to simulate this phenomenon in two dimension (2D) and Butlanska et. al.…”
Section: Introductionmentioning
confidence: 99%